The Sound of Silence: A Review Essay of Nancy MacLean’s Democracy in Chains: The Deep History of the Radical Right’s Stealth Plan for America - Fleury, Jean-Baptiste; Marciano, Alain (Journal of Economic Literature, 2018)
This essay reviews Nancy MacLean’s Democracy in Chains: The Deep History of the Radical Right’s Stealth Plan for America, which triggered a huge controversy that virally spread on the Internet and in various journals. We will evaluate MacLean’s almost biographical account of James Buchanan, which portrays the 1986 Nobel Prize laureate as the mastermind behind today’s attacks, by the foot soldiers of the radical right, on American democracy. This essay develops three main points. One, MacLean’s general narrative puts too much emphasis on Buchanan and largely neglects the many other important characters who contributed to the intellectual criticism of government intervention. Two, MacLean’s account is marred by many misunderstandings about public choice theory, for instance about the role that simple majority rule plays in constitutional economics. Third, in the midst of abundant archival material, her historical narrative is, at best, sketchy, and is replete with significantly flawed arguments, misplaced citations, and dubious conjectures. Overall, MacLean tends to overinterpret certain aspects in Buchanan’s life and thought, while she overlooks others that are equally important in understanding his work and influence. In particular, we stress that Buchanan was, first and foremost, a scholar, not a political activist, who gave significant attention to ethical considerations in his analysis of markets. ( JEL A11, B21, B31, D72, K00, N42)